ANALISIS HAMBATAN NASABAH DALAM MENGADOPSI PRODUK-PRODUK BANK SYARIAH INDONESIA: STUDY DI KABUPATEN PESAWARAN - Rizki Tri Sulam; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study aims to analyze the obstacles faced by customers in adopting Islamic bank products Indonesia. Although the growth of Islamic banking has shown a positive trend, the market share of Islamic banks is still relatively small compared to conventional banking. This study uses a qualitative approach by conducting in-depth interviews with 22 Islamic bank customers and 13 conventional bank customers in Pesawaran Regency. The results of the study identified several obstacles found including: 1) Lack of education from Sharia Banking, 2) Human Resources (HR), 3 Public Understanding of Sharia Banking, and 4) Public Interest in adopting Sharia Banking products. This study recommends several strategic interventions, as well as increasing Islamic financial literacy. This finding is expected to provide a change in knowledge for regulators and Islamic banking industry players in formulating policies and strategies to increase the adoption of Islamic bank products in Indonesia.